Regime diferenciado de contratações públicas principais inovações no regime de contratações públicas - Negrette, Silvia Cristina Gil Ribeiro (2015)
This work intends to present, even briefly, the main innovations brought by Regime Diferenciado de Contratações – RDC (Federal Law nº 12.462/2011), especially comparing to the traditional bidding process established by Lei Geral de Licitações e Contratos Administrativos (Federal Law nº 8.666/1993). At first, and under the perspective of the classical model of bidding, the law seems quite modern novel, full of new institutes and simplified procedures; however, as will be seen throughout the monograph, the RDC compiles many similar or even common instruments already known new laws in this issue, like Federal Laws nº 8.987/1995, nº10.520/2002, nº 11.079/2004, among others